Challenges in Developing English As A Second Language (ESL) Learners’ Reading Skills in Pakistan: A Systematic Literature Review - Ishfaque Ali Kalhoro; Mimi Nahariah Azwani Mohamed; Muhammad Nadzrin Khairuddin (Journal of Social Transformation and Regional Development, 2025)
Teachers in Pakistan face numerous challenges in developing the reading skills of English as a Second Language (ESL) learners due to various factors. Despite their teaching efforts, students’ reading comprehension skills remain at an unsatisfactory level. This paper presents a systematic literature review exploring the complexities of developing reading skills among second language learners in Pakistan. The review employs the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) technique, which provides standardized strategy for discovering, screening, and selecting relevant studies while assuring transparency and comprehensiveness in the review process. The study focusses on studies published between 2016 and 2024. The review reveals that one of the main challenges in enhancing ESL learners’ reading comprehension skills is the teaching strategies employed by the teachers. Studies indicate that teachers often rely on translation-based instruction, which is considered ineffective. Another significant challenge is the low motivation among ESL learners. These insights highlight the need to equip Pakistani teachers with effective methods for teaching reading skills and to boost learners’ motivation in second language learning, thereby fostering a stronger reading culture in schools.